Grounded Theory: The FAQs. Issue 1 (17th October 2019) - Birks, Melanie; Hoare, Karen; Mills, Jane
Since being developed as a research methodology in the 1960s, grounded theory (GT) has grown in popularity. In spite of its prevalence, considerable confusion surrounds GT, particularly in respect of the essential methods that characterize this approach to research. Misinformation is evident in the literature around issues such as the various approaches to GT, how long the process takes, the role of literature and preconceptions, generating and using data and strategies to produce theory. This article examines the most frequently asked questions about GT in an effort to demystify its purpose and use. Understanding the fundamental concepts of GT is critical to the correct use and application of GT methods and the ultimate production of theory that is grounded in data. More significantly, this understanding can prevent researchers encountering common pitfalls that can impede the process and impact the products of research.